PROINFLAMMATORY CYTOKINE EXPRESSION AS A EARLY DIAGNOSTIC MARKER FOR DETECTION OF SUB CLINICAL ENDOMETRITIS IN REPEAT BREEDER CROSSBRED COWS - U S, KALYAAN; K, KULASEKAR; JOSEPH, CECILIA; S, VAIRAMUTHU; P, RAJA; T M A, SENTHIL KUMAR (The Indian Journal of Animal Reproduction, 2023)
A clinical study was carried out in a group of crossbred cattle with the history of repeat breeding. Ten apparently healthy cows having a normal calving history and clear estrual mucus discharge were selected as Control (Group I).Ten repeat breeder cows with watery,cloudy, copious discharge suspected for sub clinical endometritis (SEND) were selected for the study (Group II). These cows were subjected to gene expressionstudies of pro inflammatory cytokines IL - 8 and TNF a from endometrial biopsy samples using qPCR and their expression was found to be increased compare to control groups, thus indicating that pro inflammatory cytokines such as ILB and TNF a can be used as a diagnostic indicator for SEND.
Keywords: Repeat breeders; SEND; Inflammatory cytokines